PARENTAL SUPPORT FOR EARLY CHILDREN SUFFERING PICKY EATING - Tria Wahyuningrum (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The nutritional status of children is crucial for promoting optimal growth and development. Picky food is one of the obstacles to achieving optimal nutritional status. Children who suffer from selective eating will develop the habit of selecting particular foods to consume and rejecting others. The purpose of this research is to examine familial assistance for children who suffer from picky eating. This study is a component of qualitative research that employs in-depth interviews with parents serving as informants. Additionally, observations were conducted on subjects, specifically children who exhibited picky feeding behavior. To gather data regarding selective eating, the Child's Eating Behavior Questionnaire (CEBC) was utilized. The subjects of the study were selected using a technique known as purposive sampling, in accordance with the research criteria: early infancy age, picky eating, and informant willingness to participate. A total of ten informants were acquired. Picky eaters are children who have developed the ingrained habit of declining novel food items. Children are fond of the flavor and texture of particular dishes. Children have a tendency to prefer the same foods and are unwilling to attempt new variations. The subjects of the study were five infants (fifty percent each) with excessive and normal nutrition. Children who exhibit picky feeding tend to select nutrient-poor, high-fat foods, resulting in overnutrition. The fact that certain foods cause fluctuating preferences in some children has no bearing on BB and TB. In response to a child's dislike of food, parents discontinue nourishment. When children exhibit a reluctance to try new cuisines, their parents attempt to console them without altering the food's appearance. Snacks are frequently provided to children who decline to consume staple foods. Support from parents is correlated with the food behavior of children who suffer from picky eating. Parents are encouraged to address this issue by selecting foods that meet the nutritional requirements of their children.